Deconstruction of the Surgical Approach to the Jugular Foramen Region: Anatomical Study - Basma, Jaafar; Michael, L. Madison, II; Sorenson, Jeffrey M.; Robertson, Jon H. (Journal of Neurological Surgery Part B: Skull Base, 2019)
Introduction The jugular foramen occupies a complex and deep location between the skull base and the distal-lateral-cervical region. We propose a morphometric anatomical model to deconstruct its surgical anatomy and offer various quantifiable target-guided exposures and angles-of-attack.Methods Six cadaveric heads (12 sides) were dissected using a combined postauricular infralabyrinthine and distal transcervical approach with additional anterior transstyloid and posterior far lateral exposures. We identified anatomical landmarks and combined new and previously described contiguous triangles to expose the region; we defined the jugular and deep condylar triangles. Angles-of-attack to the jugular foramen were measured after removing the digastric muscle, styloid process, rectus capitis lateralis, and occipital condyle.Results Removing the digastric muscle and styloid process allowed 86.4° laterally and 85.5° anteriorly, respectively. Resecting the rectus capitis lateralis and jugular process provided the largest angle-of-attack (108.4° posteriorly). The occipital condyle can be drilled in the deep condylar triangle only adding 30.4° medially. A purely lateral approach provided a total of 280.3°. Cutting the jugular ring and mobilizing the vein can further expand the medial exposure.Conclusion The microsurgical anatomy of the jugular foramen can be deconstructed using a morphometric model, permitting a surgical approach customized to the pathology of interest.
Keywords: jugular foramen; far lateral; infralabyrinthine approach; styloid process; occipital condyle; cranial nerves; distal cervical approach